Sustentabilidade cultural no âmbito do desenvolvimento local - uma análise do DLIS/SEBRAE-SE - Nascimento, Mirian Guedes (2005)
The northeast part of Brazil has been the stage for many public policies which are presented as a solution to make the regional economy dynamic and promote the improvement of the quality of life of the population. The execution of the methodology DLIS (Desenvolvimento Local Integrado e Sustentável) Integrated and Sustainable Local Development stands out in this context defining local development strategies through the participation of the communities. From the participative diagnosis in which local problems, vocations and potentialities are pointed out, a development plan is elaborated and a local agenda is extracted. The priority actions of this agenda must be executed by many partners of federal, state and municipal spheres and local civil society organizations. This methodology has been introduced in 26 of the 75 Brazilian municipalities. In the state of Sergipe, it is particularly performed by SEBRAE (Serviço Brasileiro de Apoio às Micro e Pequenas Empresas) - Brazilian Micro and Small Business Support Service. The development plans, mainly those whose action scale is the locality, can in fact contribute to local sustainable development, if the geographical, political, cultural and historical singularities are considered, and if the participation of all the development actors is assured. Our work is focused on the evaluation of DLIS methodology, without understanding it as a certifiable model of sustainable development to be pursued for all the municipalities. In accordance with our understanding of the importance of this methodology as a development policy and with the necessity of evaluating it under the concrete perspective of its contents, our work attempted to evaluate the impacts of the actions introduced by DLIS/SEBRAE concerned with cultural sustainability and local participation, seen as essential to local sustainable development, taking as case study the municipality of Canindé do São Francisco, in the state of Sergipe and, for that, we considered some setbacks. We analysed that the way of life, the cultural values and the local social actors identities were not taken into consideration in this process. The expectations in relation to local sustainable development were not considered, as well. We have also analysed the insertion degree of local social actors in the participative process and the treatment given to the locality by the methodology. We see this study as a contribution to the evaluation of participative social policy methodologies through a new relation between state and society, and also, as a fertile theme that points out the insertion of the cultural dimension in development plans. The results can be relevant even for policy makers, local development financiers and for non-governamental organizations interested in knowing the impacts of these actions from the evaluation and perception of the alleged beneficiaries.